MACROECONOMIC ASPECTS OF THE ANALYSIS OF THE WORLD MARKET OF SPACE PRODUCTS AND SERVICES - A. Krishtofor (Вестник университета, 2019)
The main organizational characteristics of the world space industry in the context of increased international competition have been determined. The most characteristic changes in the global market of space products have been identified. The methodology of the analysis of the world market of space products and services has been presented. As a result of the analysis of the successful international experience in the development of the space industry and the trends of the world space activity, the global patterns, that need to be taken into account in the implementation and planning of measures to improve the competitiveness of space activity of the Russian Federation have been revealed.